Nilai Sosial Budaya dan Pendidikan dalam Film "Keluarga Cemara" - Evi Sudiawati; Maria Immaculata Adhisti Prima (Diskursus: Jurnal Pendidikan Bahasa Indonesia, 2022)
The purpose of the study was to identify the types of socio-cultural and educational values found in the film Fir Family using the semiotics study of Charles Sanders Pierce's concept. Data is obtained from screenshots of each scene and dialogue that contains socio-cultural and educational values. Cemara Family film contains 6 socio-cultural values according to Spinger, namely theory, economics, solidarity/gotong-royong, religion, art, and power. As for the value of education there are 9 educational values from 12 educational values according to El Mubarok. Found 4 educational values that belong to the category of embodied values. These values include the values of courage, peace, confidence and potential, as well as naiveness. On the other hand, there are 5 educational values that fall into the category of giving values. These values include loyalty and trust, respect, love and compassion, selflessness and kindness and kindness are found in film scenes and dialogue. Cemara Family is a film released in 2019 directed by Yandi Laurens and the main cast of this film is Abah played by Ringgo Agus Rahman. Mother, played by Nirina Zubir. Euis is played by Zara JKT48, and Ara is played by the daughter of singer Widy B3, Widuri Putri Sasono. The film Keluarga Cemara emphasizes the 'true story' of young Indonesian families who must dare to slam the steering wheel when the main job that has been pursued so far must fall because of various problems. From being a Director in a company, to being a building porter to becoming a Gojek motorcycle driver to keep supporting existing families. It's not the pain emphasized in the film, but the ability to survive sustaining a family in the midst of limitations. Keywords: Semiotics study, Charles Peirce theory, Fir Family film, type of socio-cultural value, type of educational value